Modified colony indirect epifluorescence test for serotyping Ureaplasma urealyticum and an adaptation to detect common antigenic specificity. - Stemke, G W (1981)
A microtiter method for efficiently serotyping colonies of Ureaplasma urealyticum by immunofluorescence is described. Prior detergent treatment allowed identification of common group determinants.